A New Genus and Species of Phtisicidae (Crustacea: Amphipoda) from Abyssal Depths in the Japan Trench, with Special Reference to Similarities with Southern Ocean Genera. Issue 4 (1st July 2016) - Takeuchi, Ichiro; Tomikawa, Ko; Lindsay, Dhugal
Abstract: Abyssododecas styx, a new genus and new species of Phtisicidae (Amphipoda), is described based on specimens collected from cold-seep sites at abyssal depths between 5313 and 7322 m in the Japan Trench, North Pacific, using the crewed submersible Shinkai 6500 and the Remotely-Operated Vehicle Kaiko . This is the deepest yet record of a caprellidean amphipod. While A. styx n. gen., n. sp. looks like a member of Caprellidae, this species can be assigned to Phtisicidae through the possession of a normally articulated pereopod 3 and the lack of a molar on the mandible. The distribution of Phtisicidae along the coast of Japan, including deep-sea habitats, is rather rare, whereas genera of Caprellidae are dominant. Abyssododecas n. gen. is most closely-related to Dodecasella K. H. Barnard, 1931, which is distributed in the Southern Ocean, but differs in possessing a 2-articulated flagellum on antenna 2. The present discovery of Abyssododecas n. gen. from the North Pacific suggests a northward-trending distribution pathway over the ocean floor over geological time into the North Pacific through transport by Antarctic Bottom Water.